2020
DOI: 10.3389/fgene.2020.00684
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Reveals miRNA Role Shifts in Seven Stages of Skeletal Muscles in Goat Fetuses and Kids

Abstract: MicroRNAs (miRNAs) are indispensable for the regulation of skeletal muscle. We performed RNA sequencing (RNA-seq) to establish a comprehensive miRNA profiling of goats in seven stages, namely, 45-(F45), 65-(F65), 90-(F90), 120-(F120), and 135-day (F135) fetuses, newborn (B1), and 90-day-old (B90) kids. In total, 421 known miRNAs and 228 goat novel miRNAs were identified in the data, and the average abundance of 19 miRNAs in seven stages exceeds 10,000 reads per million. Furthermore, 420 differentially expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
(57 reference statements)
3
12
0
Order By: Relevance
“…Muscles have an incredible ability to change their functional characteristics in order to adapt and function optimally in response to the physiological state of the animal (e.g., growing, maintaining, or senescing). The regulatory non-coding RNAs at different stages of muscle development in multiple species are gradually being revealed, such as duck [ 14 ], sheep [ 15 ], pig [ 16 ] and goat [ 17 ]. For example, 1,498 circRNAs were identified in the skeletal muscles of pigs at three stages after birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscles have an incredible ability to change their functional characteristics in order to adapt and function optimally in response to the physiological state of the animal (e.g., growing, maintaining, or senescing). The regulatory non-coding RNAs at different stages of muscle development in multiple species are gradually being revealed, such as duck [ 14 ], sheep [ 15 ], pig [ 16 ] and goat [ 17 ]. For example, 1,498 circRNAs were identified in the skeletal muscles of pigs at three stages after birth.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the continuous stage and unique expression differential circRNAs and their potential functions have also been explored [ 16 ]. In addition, the dynamic expressions of miRNAs and lncRNAs in 7 stages of goat was revealed, which have the potential to affect skeletal muscle development [ 17 , 18 ]. Therefore, exploring the regulatory molecules of muscle physiological changes at different stages is equally essential for the breeding of meat rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wang et al identified 336 differentially expressed miRNAs in skeletal muscle of Huanghuai goats between fetal stage and 6-month-old stage, of which miR-424-5p, miR-29a, miR-129-3p, miR-181b, and miR-181d were involved in multiple important pathways related to muscle development ( 18 ). Guo et al and Ling et al also found some important differentially expressed miRNAs in skeletal muscle from prenatal stages to neonatal stage in Jianzhou Da′er goats and Anhui white goats ( 19 , 20 ). However, little is known about the miRNA profiles of muscle tissues in other goat breeds, or between different goat breeds.…”
Section: Introductionmentioning
confidence: 94%
“…An aliquot of 3 μg of total RNA per sample was used as input material for generation of a small RNA library. Sequencing libraries were generated using a NEBNext ® Multiplex Small RNA Library Prep Set for Illumina ® (NEB, Ipswich, MA, USA) following the manufacturer's recommendations, and the index codes were added to attribute sequences to each sample (Ling et al 2020). The library quality was assessed by an Agilent 2100 Bioanalyzer System (Thermo Fisher Scientific, Waltham, MA, USA) using a high-sensitivity DNA chip.…”
Section: Rna Extraction and Small Non-coding Rna Sequencingmentioning
confidence: 99%